A influência da prática de futebol na cultura de jovens indígenas Xerente. - Xerente, Ronan Warõmekwa de Brito (Universidade Federal do Tocantins, 2021)
The present work aimed to verify the influence of football in the cultural practices of young Xerente indigenous people who live in the municipality of Tocantínia - TO near the capital Palmas. The method for verifying this influence consisted of applying an interview through a semi-structured questionnaire with students members of the Xerente indigenous communities, and thus obtaining the information to be able to verify if in any way football ends up having the due influence on cultural practices of Xerente indigenous youth. The data were described according to descriptive statistical analysis, in terms of frequency distribution of responses, mean and standard deviation of the mean, treated in Excel's own analysis tools. And from the use of categories and response codes, according to content analysis formulated by Bardin (2009). When assessing the responses of school-age indigenous youth at the institution of the